2022
DOI: 10.1371/journal.pone.0272628
|View full text |Cite
|
Sign up to set email alerts
|

The pattern and use of Twitter among dental schools in Saudi Arabia

Abstract: Objective Twitter as a social media platform has revolutionized the way we interact with others and receive information. The presence of dental schools in Twitter facilitates the engagement of students, educators, dental professionals, and the community. Given the explosive popularity of Twitter as a social media platform and its potential use in the areas of education and branding, the questions of why and how dental schools use these services warrant comprehensive research. Thus, the aim of this study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
1
0
0
Order By: Relevance
“…Quick feedback fuction can contribute to improving the use of Twitter for decimating important information to students. This is also parallel with the findings of previous study that showed Twitter can improve the spread of information to the students which was conducted on a different topic (Al-Khalifa et al, 2022). Another benefit of using Twitter is the ability to share messages with other users or followers (Reyna et al, 2022), which in this case, refer to the students.…”
Section: Using Twitter To Decimate Information Outside Of the Classroomsupporting
confidence: 86%
“…Quick feedback fuction can contribute to improving the use of Twitter for decimating important information to students. This is also parallel with the findings of previous study that showed Twitter can improve the spread of information to the students which was conducted on a different topic (Al-Khalifa et al, 2022). Another benefit of using Twitter is the ability to share messages with other users or followers (Reyna et al, 2022), which in this case, refer to the students.…”
Section: Using Twitter To Decimate Information Outside Of the Classroomsupporting
confidence: 86%